(untitled) (Quinto Sol, 2013)
This paper attempts to analyze the Argentinian official policies for the settlement of the indigenous survivors after 1879-1885 military campaigns, and the results of such policies, focusing in the study of the genesis, organization and development of the pastoral colony Emilio Mitre in La Pampa Territory, during the first decades of its existence.